Synthesis and characterization of novel water‐soluble and bactericidic cationic starch esters. (6th April 2017) - Pfeifer, Annett; Hampe, Robert; Heinze, Thomas
Abstract : Novel water‐soluble cationic starch esters, namely starch‐4‐( N, N, N ‐trimethylammonium)butyrate chloride with high degree of substitution (DS) of up to 0.7 could be easily prepared by conversion of starch of different molar mass with the imidazolide of 3‐carboxypropyltrimethylammonium chloride (CPTMACl) homogeneously in dimethyl sulfoxide (DMSO). The products were characterized in detail by FTIR and NMR spectroscopy, including two‐dimensional methods. The cationic starch esters possess a high antibacterial activity.